Sheffield in the Great War - Warr, Peter G. (Your towns and cities in the Great War., 2015)
This fascinating new book is devoted to an almost unknown period in the history of Sheffield. It sets the city's people and events against a background of key national developments by looking also at the way government regulations were tightened, how the country's morale was maintained, and how industry was encouraged to deliver more output. Sheffield in the Great War is written for the general reader, and a large number of the city's residents, companies and streets are mentioned by name. Many aspects of life and work are described and illustrated with more than one hundred original photogra.